2017
DOI: 10.1002/term.2477
|View full text |Cite
|
Sign up to set email alerts
|

Haemodynamically stimulated and in vivo generated axially vascularized soft‐tissue free flaps for closure of complex defects: Evaluation in a small animal model

Abstract: The arteriovenous (AV) loop model permits the creation of significant volumes of axially vascularized tissue that represents an alternative to conventional free flaps, circumventing their common limitations. However, such AV loop-based flaps have never before been examined in standardized animal models with respect to their suitability for reconstruction of critical bone-exposing defects. In the course of our preliminary studies, we implemented a novel defect model in rats that provides standardized and critic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 30 publications
0
16
0
Order By: Relevance
“…The data presented here may also be applicable in future translational studies in the field of tissue engineering. The AV loop model is a reliable tissue engineering technique for creation of vascularized and transplantable soft tissue units and has a great potential for successful translation from animal models into clinical trials in the future [82]. The miRNA profile and specific candidate genes we report, can serve as targets for selective enhancement of neovascularization using synthetic miRNA-mimics or antagomirs.…”
Section: Discussionmentioning
confidence: 99%
“…The data presented here may also be applicable in future translational studies in the field of tissue engineering. The AV loop model is a reliable tissue engineering technique for creation of vascularized and transplantable soft tissue units and has a great potential for successful translation from animal models into clinical trials in the future [82]. The miRNA profile and specific candidate genes we report, can serve as targets for selective enhancement of neovascularization using synthetic miRNA-mimics or antagomirs.…”
Section: Discussionmentioning
confidence: 99%
“…In the context of tissue engineering, the creation of an AVL by interposing a vein graft between the saphenous vein and artery can be used for axial neovascularization of bioartificial tissue. Within the AVL, the autologous interposed vein graft is exposed to an arterial flow pattern, which stimulates angio-inductive properties and promotes neovascularization [ 21 , 43 ]. Recent studies have shown that the vein graft is the crucial effector of early angiogenesis during the neovascularization of a fibrin matrix [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…The AVL chamber model facilitated the investigation of human placenta vessel engraftment in a high-flow system isolated from the surrounding tissue. Briefly, each AVL was generated using a decellularized human placenta vessel graft (hPG) anastomosed end-to-end between the right saphenous artery and vein with 11-0 Ethilon sutures (Ethicon, Somerville, NJ, USA) as previously published [ 21 ]. The AVL was subsequently placed into an isolation chamber and embedded in 2 layers of Matriderm ® , an acellular dermal matrix consisting of bovine collagen and elastin ( Figure 2 A–F).…”
Section: Methodsmentioning
confidence: 99%
“…In 2012, Ding et al 8 further modified the arteriovenous loop for flap prefabrication by anastomosing the rat's caudal vein graft to the superficial iliac circumflex vein and the femoral artery. In 2018, Schmidt et al 17 combined arteriovenous loop with tissue engineering to prefabricate flaps that successfully repaired a distant complex tissue defect in rats. These reports show an arteriovenous loop can serve as a vascular pedicle for flap prefabrication.…”
Section: Discussionmentioning
confidence: 99%